2018
DOI: 10.1177/0308518x18786726
|View full text |Cite
|
Sign up to set email alerts
|

Partner choice in Sweden: How distance still matters

Abstract: Spatial homogamy, or the geographical closeness of life partners, has received little attention in recent decades. Theoretically, partners may be found anywhere in the world, as increases in educational participation, affluence, mobility and internet access have reduced the meaning of geographical distance in general. This paper examines whether geography still matters in the current Swedish partner market. Register data are used to track the residential histories (1990-2008) of couples who married or had a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 79 publications
0
13
1
2
Order By: Relevance
“…Based on survey data, Niedomysl (2011) reported that social reasons for moving, including union formation, are prominent across all moving distances in Sweden. Half of all partners who later married or had a child in the 1990s and 2000s, lived within 9 km of each other before moving in together (Haandrikman 2015). In the same study, distances moved were shortest in urban areas, for those with parents nearby, and for those born abroad.…”
Section: Introductionmentioning
confidence: 99%
“…Based on survey data, Niedomysl (2011) reported that social reasons for moving, including union formation, are prominent across all moving distances in Sweden. Half of all partners who later married or had a child in the 1990s and 2000s, lived within 9 km of each other before moving in together (Haandrikman 2015). In the same study, distances moved were shortest in urban areas, for those with parents nearby, and for those born abroad.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the largest cities are a magnet to university graduates from everywhere (see Grimes et al, 2020, for New Zealand evidence) while partnering remains even in today's online dating world a phenomenon largely determined by colocation or at least by short geographical distances. Hence besides a prevalence of homogamy in terms of age, education, and so on, there is also spatial homogamy (see e.g., Haandrikman, 2019, for evidence from Sweden). The interrelationship between spatial homogamy, migration, and personal attribute homogamy is yet is be studied but would be most fruitfully conducted with longitudinal data rather than with the census data used in the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…The area around lake Vättern (Fig. 2b), that may be seen as being part of the Bible Belt, characterized by relatively high church attendance, a high share of voters for the Christian democrat party and a high share of small firms and self-employment (Haandrikman, 2019), is characterized by higher shares of fathers' care leave in built up areas, but lower shares in rural areas. Kiruna, in the far north of the country, is a small town in an otherwise sparsely populated area, as seen in Fig.…”
Section: Geographical Variation In Fathers' Uptake Of Care Leavementioning
confidence: 99%